Lithiotid Bivalves in Slovenia and Their Mode of Life - Buser, Stanko; Debeljak, Irena (Geologija, 1997)
Lithiotid bivalves are a characteristic faunal element of the shallow marine facies of Lower Jurassic beds in Southern Slovenia. The horizon containing Middle Liassic bivalves, which is up to 75 m thick, is called the “lithiotid horizon” and is attributed to the Pliensbachian or Domerian. In Slovenia the name lithiotid bivalves represents three morphologically similar genera or species of sessile monomyarian dysodont bivalves: Lithiotis problematica, Cochlearites loppianus and Lithioperna scutata, which are systematically examined in this paper. The term lithiotid bivalves does not have any taxonomic significance, since they are now classified in different families. The order is Pterioida. Lithiotid bivalves lived in an upright position on soft lagoonal bottoms in a tight aggregate of individuals crowded together which mutually supported one another and simultaneously competed for living space and light. The sedimentation of calcareous mud was fairly rapid, thus throughout their lives they grew constantly in a subvertical direction so that the small soft body space at the ventral end remained above the level of the-surrounding -substratum. Lithiotid bivalves had peculiar, variable shells adapted to the specific environment. They are very large, fiat and distinctly dorso-ventrally elongated. Their inner surface is tripartite; in the middle is the central area, and at the sides there are feather-like areas. The mechanism of opening and closing their valves has not yet been fully explained.